Genome-wide analysis of miRNAs and their target genes in wheat cultivars with different ploidy levels under drought stress - Ulu, Ferhat; Unel, Necdet Mehmet; Baloglu, Mehmet Cengiz (Springer Science and Business Media LLC, 2025)
Abstract Main conclusion This study provides novel insight into the role of miRNAs in the drought resistance of different wheat cultivars, revealing a correlation between ploidy level and drought tolerance. Abstract MicroRNAs (miRNAs) are endogenous, mostly conserved, non-coding regulatory RNAs with 20–24 nt in length. Although many studies have been conducted on miRNAs that play a role in wheat drought stress response, there are no comparative studies in wheat cultivars with different ploidy levels. Here we compared miRNAs profiles of three wheat cultivars with different chromosome numbers and drought resistance levels using miRNAome and qRT-PCR analysis. Bioinformatics analysis showed that all cultivars shared 93 miRNAs in the control leaf, while 91 miRNAs were shared in stress-treated leaf groups. A total of 90 and 92 miRNAs were expressed by all cultivars in control and stress root samples, respectively. Also, 17 and 21 miRNAs were expressed species-specifically in control and stress leaf, whereas 23 and 20 were expressed in control and stress root groups, respectively. Also, tae-miR159a and tae-miR167c expressions showed drought resistance increases as the ploidy level rises, and Triticum aestivum and Triticum turgidum are more tolerant than Triticum monococcum. Furthermore, according to in silico analysis 729 and 771 genes were targeted in control-leaf and stress-leaf groups of all cultivars; also, 775 and 776 genes were targeted in control-root and stress-root samples by determined miRNAs, respectively. Additionally, degradome data showed 351 and 356 genes were targeted in leaf and root tissues, respectively. These findings propose that genotypic variation is responsible for the differential expression of miRNAs and the target genes in drought stress response. The results could serve as a guide for future research on the drought response mechanism.
Keywords: Original Article